Defining the decision‐to‐delivery interval at caesarean section: narrative literature review and proposal for standardisation. (8th September 2021) - May, R. L.; Clayton, M. A.; Richardson, A. L.; Kinsella, S. M.; Khalil, A.; Lucas, D. N.
Summary: The decision‐to‐delivery interval is a widely used term at non‐elective caesarean section. While the definition may appear self‐evident, there is no universally agreed consensus about when this period begins and ends. We reviewed the literature for original research utilising the terms 'decision‐to‐delivery', 'decision‐to‐incision' or 'incision‐to‐delivery' and examined definitions used for decision, delivery, incision, as well as any additional time intervals that were assessed. Our analysis demonstrated an inconsistent non‐standardised approach to defining these intervals, which might have clinical practice and medicolegal ramifications. We propose that the decision‐to‐delivery interval should be defined as follows: the interval between the time at which the senior obstetrician makes the decision that a caesarean section is required and the time at which the fetus (or first fetus in the case of multiples) is delivered. The decision time should ideally be recorded contemporaneously in the medical notes or partogram.